Satisfaction, willingness, and well-being: Examining the perceptions of a statewide sample of public and private foster parents. (February 2021) - Griffiths, Austin; Holderfield-Gaither, Emily; Funge, Simon P.; Warfel, Erin T.
Abstract: Foster parents are a critical resource and make a significant difference in the lives of children. This article examines the quantitative feedback on the Foster Parent Perception and Satisfaction Scale (FPPSS) from a statewide sample of public and private foster parents (n = 255) in a southern state. Results indicate that perceptions of accomplishment and personal impact were the primary predictors of overall role satisfaction. However, the foster parents' willingness to accept the placement of a child that is a) LGBTQ or b) different than themselves (e.g. religion, race/ethnicity, and other requested preferences such as age, special need, sibling group) also significantly predicted their overall satisfaction though inversely with respect to LQBTQ foster children. Significant differences were found between the public and private foster parents with respect to their satisfaction with their state caseworker, preparedness, foster agency, overall level of satisfaction, and their willingness to accept the placement of a teenager and of a child with a difference. Implications for training further research with public and private foster agencies are provided.